The role of impression management in enhancing organizational citizenship behavior - an analytical study of the opinions of a sample of teachers in government colleges - Meethaq Hatif Al-Fatlawii,; Karar Nizar Nouri football, (Iraqi Journal for Administrative Sciences, 2024)
The objective of this research is to identify the role of impression Management in enhancing organizational citizenship behavior of a sample of the teaching staff in the four state colleges amounted to (121) of teaching and to achieve the goal of research and through access to research and foreign studies researcher adopted global standards for measuring research variables, as it has been relying on model (Bolino & Turnley:1999) to represent the dimensions of impression management(Self-promotion, ingratiation, exemplification, intimidation supplication,) was relying on the model (Dickinson: 2009) to represent the dimensions of organizational citizenship behavior (altruism, consciousness, courteous , civic virtue, sportsmanship) questionnaire has been used as a key tool for data collection. In order to reach the objectives of the research were formulated A set of assumptions that include test correlation between impression and dimensions of organizational citizenship behavior management dimensions and by using a number of appropriate statistical tools such as the mean and standard deviation and coefficient of simple correlation (Pearson) was test these hypotheses. In light of this it has been reached results that impression management had a significant role in organizational citizenship behavior among a sample search at colleges surveyed (at the macro level) and recommends to work to find some kind of convictions between the dimensions of impression management and organizational citizenship behavior for the purpose of finding a distinctive ethical culture as This conviction can achieve the best image when it is based on a true convictions from the presence of Top Management.